The said and not-said: new grammar of visual imperialism - Esmaeil Zeiny,; Noraini Md Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Since the European colonization of the East, stereotypical depictions of their perceived Orient as exotically backward and Muslim women as submissive and lecherous have been appearing as major themes in Western visual discourses. These representations, manifested to justify Western presence in the East, pervade even after the tragic events of 9/11. The West, especially the United States, now has to exercise new strategies to justify their imperial ‘war on terror’ project. The post-9/11 Western mass media and visual discourses are still fraught with stereotypes that consolidate stereotypical representations. Thus, by deconstructing the layers of Western misrepresentations of the Orient and studying the history of visual imperialism, this paper investigates, in the course of post-9/11 contexts, the grammar of visual imperialism in representing the East and Muslims have both negative and positive depictions. However we reveal that even the positive depictions would eventually consolidate the orientalist stereotypes and legitimize racist policies and practices. By drawing on Whitlock’s concept of ‘soft weapon’, we argue that using Muslim women to relate their own stories of oppression and victimhood through memoirs is another new strategy to confirm the pre-existing notions of the East. These Muslim life narratives become soft weapons when they elicit sympathy from Western readers. Therefore, while the rule in the representation of Muslims after 9/11 has changed through the use of different strategies to apparently dispel the stereotypes, they ultimately reinforce the preexisting notions about the East and Muslims.